The hybridization of Ag2CO3 rods with g-C3N4 sheets with improved photocatalytic activity - Konglin Wu; Yanwei Cui; Xianwen Wei; Xinjie Song; Jiarui Huang (Journal of Saudi Chemical Society)
A series of graphitic carbon nitride/silver carbonate (g-C3N4/Ag2CO3) rod-like composites with different weight contents of g-C3N4 have been prepared by a facile precipitation method. The g-C3N4/Ag2CO3 rod-like composites exhibited higher photocatalytic activity than pure Ag2CO3 toward degradation of rhodamine B (RhB) and methylene blue (MB) under visible-light irradiation. The photocatalytic reaction follows a pseudo-first-order reaction and the rate constants for the degradation of RhB and MB by 3.5% g-C3N4/Ag2CO3 are about 2 times and 1.7 times that of pure Ag2CO3, respectively. A possible photocatalytic mechanism was proposed based on the photoluminescence (PL) spectra and a series of radical trapping experimental analyses. The remarkably improved photocatalytic performance should be ascribed to the heterostructure between Ag2CO3 and g-C3N4, which greatly promoted the photoinduced charge transfer and inhibited the recombination of electrons and holes.